Business modeling and software design / : 9th International Symposium, BMSD 2019, Lisbon, Portugal, July 1-3, 2019, proceedings /: 9th International Symposium, BMSD 2019, Lisbon, Portugal, July 1-3, 2019, proceedings. (2019) - Unknown
No abstract available